Analysis of Government Policy in Improving the Effectiveness of Inclusive Education in Public Schools - Raya, Liana Vanessa (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2025)
This research investigates the effectiveness of government policies aimed at improving inclusive education in public schools, focusing on the barriers and challenges that impede successful implementation. Employing a mixed-methods approach, the study combines quantitative data from surveys of educators and administrators with qualitative insights from interviews and focus group discussions with stakeholders. The findings reveal significant gaps in teacher training, insufficient funding, and inadequate resource allocation, particularly in rural and low-income areas, all of which hinder the successful inclusion of students with disabilities. Additionally, societal attitudes and stigma surrounding disabilities continue to pose challenges to inclusivity. The research highlights the importance of community and parental involvement, emphasizing that active engagement can foster a more supportive and accepting educational environment. Furthermore, it underscores the necessity for a culture of continuous improvement through regular assessment and feedback mechanisms. Based on these findings, the study offers actionable recommendations for policymakers and educators to enhance the effectiveness of inclusive education practices, ensuring that all students, regardless of their abilities, receive equitable access to quality education. Ultimately, this research contributes to the ongoing discourse on inclusive education, providing valuable insights for future policy development and implementation strategies.